Interactive FEM education for load-bearing system static and dynamic analysises by case of the bionic tower of the Eddys- tone lighthouse - S. S. Dounar; A. M. Iakimovitch; O. K. Jatskevitch; A. D. Lapuka (Системный анализ и прикладная информатика)
FEM simulation of Eddystone lighthouse is provided. Incorporated bionic tower is modelled as well. Load cases including gravity force, wind thrust, water stream and 50-year wave impulse are accomplished. Stress concentrator system is described. Effect of tension stress concentrator compensation caused by gravity is showed. Low gradient stress dispensation is demonstrated for bionic tower outer surfaces. Recommendation touching places to monitor are given.Methodic experience related to interactive one-command student – professor FEM simulation of responsible load-bearing systems is collected.